Development of active and nanotechnology-based smart edible packaging systems: physical-chemical characterization - Cerqueira, M. A. (2014)
This work aims at characterising polysaccharide-based films without (GA) and with the incorporation of free natamycin (GA-NA) and natamycin-loaded in a smart delivery device consisting in poly(N-isopropylacrylamide) nanohydrogels (GA-PNIPA). Transport properties (water vapour, oxygen and carbon dioxide permeabilities), mechanical properties (tensile strength and elongation-at-break), opacity, water sensitivity (moisture content and contact angle) and thermal properties (differential scanning calorimetry and thermogravimetric analyses) were evaluated. Chemical interactions were studied by means of Fourier transform infrared spectroscopy and scanning electron microscopy was used to verify the presence of natamycin and nanohydrogel particles in the film matrix. The results show that natamycin and natamycin-loaded poly(N-isopropylacrylamide) (PNIPA) nanohydrogels can be successfully added to edible films without changing their main packaging properties. However, tensile strength decreased (p < 0.05) when both natamycin and natamycin-loaded PNIPA nanohydrogels were incorporated (from 24.44 to 17.02 and 16.63 MPa, for GA-NA and GA-PNIPA, respectively). GA-NA and GA-PNIPA films are more opaque and showed to be more sensitive to water (i.e. higher values of moisture content and decrease of contact angle) than GA films. Scanning electron microscopy images confirmed the presence of natamycin and poly(N-isopropylacrylamide) nanohydrogels in the films’ matrix. Since natamycin could be successfully released from polysaccharide-based films, the system could be used as active packaging ingredient when used free in the matrix or as smart packing when loaded with PNIPA nanohydrogels.